2016
DOI: 10.1063/1.4959990
|View full text |Cite
|
Sign up to set email alerts
|

Insights on finite size effects in ab initio study of CO adsorption and dissociation on Fe 110 surface

Abstract: Adsorption and dissociation of hydrocarbons on metallic surfaces represent crucial steps on the path to carburization, eventually leading to dusting corrosion. While adsorption of CO molecules on Fe surface is a barrier-less exothermic process, this is not the case for the dissociation of CO into C and O adatoms and the diffusion of C beneath the surface, that are found to be associated with large energy barriers. In practice, these barriers can be affected by numerous factors that combine to favour the CO-Fe … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 56 publications
0
19
1
Order By: Relevance
“…The C-O bond is stretched The adsorption energies for the clean surface are slightly larger in comparison with the ones calculated in previous work which are in the range of 1.7-2.0 eV. 14,15,17 We have shown in an earlier work 28 that this small advantage in adsorption is facilitated by a dilute coverage with negligible van der Waals repulsion between the neighbouring CO molecules. As for the surface with vacancy defect, an adsorption site in a close vicinity of the vacancy such as the one right into the vacancy and the bridge site next to it have thermodynamically less favourable adsorption energies and are unstable.…”
Section: Adsorptioncontrasting
confidence: 47%
See 3 more Smart Citations
“…The C-O bond is stretched The adsorption energies for the clean surface are slightly larger in comparison with the ones calculated in previous work which are in the range of 1.7-2.0 eV. 14,15,17 We have shown in an earlier work 28 that this small advantage in adsorption is facilitated by a dilute coverage with negligible van der Waals repulsion between the neighbouring CO molecules. As for the surface with vacancy defect, an adsorption site in a close vicinity of the vacancy such as the one right into the vacancy and the bridge site next to it have thermodynamically less favourable adsorption energies and are unstable.…”
Section: Adsorptioncontrasting
confidence: 47%
“…This topic has been revisited by a number of recent works. [23][24][25][26][27] While a dense CO-coverage (≤0.25 monolayer) is commonly considered, we have shown that the dissociation barrier is greatly reduced at a dilute coverage (up to 0.0625 monolayer), 28 due to the unrestricted relaxation of the Fe lattice. However, the presence of intrinsic defects is a likely candidate that can significantly affect the carburisation process and has not been considered yet.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…The remaining layers were kept frozen to imitate an infinite bulk. It is shown in reference that the structure relaxation for the reconstruction of the surface converges over a depth of less than five layers. This can be seen in Table .…”
Section: Methodsmentioning
confidence: 99%